(untitled) (Medicine Today, 2015)
This cross sectional study was carried out in the department of Radiology & Imaging, BIRDEM, Dhaka, from January 2012 to December 2012 to find out the sensitivity of thickened renal fascia in diagnosis of acute pancreatitis at CT. Total 50 patients (mean age was 41.64 years with range from 18 to 65 years, 34M/ 16F) with clinical suspicion of acute pancreatitis included in this study after analyzing selection criteria. Total 32(64%) of the 50 clinically suspected cases were diagnosed as acute pancreatitis according to the criteria mentioned in material and methods. The mean thickness of renal fascia in acute pancreatitis was 7.20 ± 3.32 mm (mean±SD) with range from 1 to 13 mm and maximum 18(40%) patients were found having thickened fascia within 4.0 to 6.9 mm. The extension of acute panceatitis only in left side was 71.8%. In 21.8%, the extension was bilateral. In 3.1% the renal fascial thickening was present on right side only .In the remaining 3.1%, renal fascia was not thickened.In 31 (96.8%) patients, the process extended into the anterior pararenal space. Both anterior and posterior renal fascia thickening was observed in 2(6.2%) patients. Normal thickness of renal fascia was found in 1(3.1%) patient. Sensitivity of thickened renal fascia in diagnosis of acute pancreatitis at CT was found 97%, specificity 50%, accuracy 80%, positive predictive value77%, negative predictive value 90%.It can be concluded that renal fascia thickening is an important as well as sensitive (97%) CT feature in the diagnosis of acute pancreatitis. Medicine Today 2015 Vol.27(1): 4-7